Analisis Pemecahan Masalah Materi Tekanan Zat Padat Berdasarkan Gender di SMPN 6 Kupang Tengah Satap - Nekleu, Ermalinda; Maing, Claudia M.M; Asamani, Fourlens H. C (STKIP HARAPAN BIMA, 2026)
This study aims to describe students’ problem-solving abilities regarding pressure in solids by examining differences based on gender. The research design employs a qualitative approach to gain a deep understanding of the phenomenon. The research procedure began with administering an initial test to all students, followed by the selection of subjects through purposive sampling. The objects of this research were four ninth-grade students (two males and two females) at a public junior high school in Kupang Regency. Data collection techniques were carried out through open-ended essay tests designed based on Polya's problem-solving indicators. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and drawing conclusions. The results showed that male students tend to be more systematic in understanding problems and planning solutions but are less thorough in unit conversion. Meanwhile, female students understand the basic concepts well but face obstacles in calculation consistency. The conclusion of the study indicates that female students possess higher metacognitive abilities and accuracy in reviewing results compared to male students.